A study on the motor control of the extraocular superior oblique and inferior rectus muscles in albino rats using the fluorescent tracers fluorogold and DiI (1,1'-Dioctadecyl-3,3,3',3'-Tetramethylindo-Carboyanine Perchlorate) (Faculty of Medicine Universitas Indonesia, 1995)
[no abstract available]